INSTITUTIONAL DETERMINANTS OF VENTURE CAPITAL ACTIVITY: AN EMPIRICALLY DRIVEN LITERATURE REVIEW AND A RESEARCH AGENDA. (27th May 2019) - Grilli, Luca; Latifi, Gresa; Mrkajic, Boris
Abstract: Venture Capital (VC) was born and has flourished in the United States, yet it has only modestly developed in other geographical areas. A vast body of research has been carried out to investigate the factors which are conducive to VC activity, and that may better explain the differences in the degree of development and performance of VC industry across different geographical contexts. However, there has only been a limited effort in the literature to systematize what we know (and what we do not know) about the institutional factors that spur VC activity. This paper tries to close that gap, through a systematic survey of the existing literature on the institutional and related determinants of VC activity. Grounding on the seminal work of North (1990), we consider formal (e.g. laws and formal rules) and informal (e.g. cultural norms and tacit codes of behaviour) institutions which are found in the extant empirical economics and management literature to affect the development of the VC industry. Building on this careful review, our paper aims to propose interesting avenues for future research in this domain.